A Robust Approach to In Situ Exsolve Highly Dispersed and Stable Electrocatalysts. Issue 11 (17th January 2022) - Wang, Mengchu; Zhang, Bike; Ding, Jiaqi; Zhang, Fanxing; Tu, Rui; Bernards, Matthew T.; He, Yi; Xie, Pengfei; Shi, Yao
Abstract: Catalysts made of in situ exsolved metal nanoparticles often demonstrate promising activity and high stability in many applications. However, the traditional approach is limited by perovskites as prevailing precursor and requires high temperature typically above 900 K. Here, with the guidance of theoretical calculation, an unprecedented and substantially facile technique is demonstrated for Cu nanoparticles exsolved from interstitially Cu cations doped nickel‐based hydroxide, which is accomplished swiftly at room temperature and results in metal nanoparticles with a quasi‐uniform size of 4 nm, delivering an exceptional CO faradaic efficiency of 95.6% for the electrochemical reduction of CO2 with a notable durability. This design principle is further proven to be generally applicable to other metals and foregrounded for guiding the development of advanced catalytic materials. Abstract : A robust and general approach for in situ highly dispersed nanoparticles exsolution from the interstitial space of a NiOOH framework at room temperature with ≈20 min is presented. Cu NPs catalyst prepared by the approach delivers an exceptional CO faradaic efficiency of 95.6% for the electrochemical reduction of CO2 with a notable durability.